Rancang Bangun Website Sekolah Menengah Pertama (SMP) Negeri 8 Kota Pagar Alam - Alfis Arif; Yogi Mukti (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2017)
Design (design) is the stage of after analysis of the system development cycle that is the definition of functional requirements, and describes how a system was established to be a depiction, planning and making sketches or arrangement of several separate elements into a unified whole and functioning, including regarding configuring of hardware components and software from a system. The goal of researchers is to design and build the website system SMP Negeri 8 Kota Pagar Alam by using the programming language PHP and MySQL. Easing the benefits of this research is to know the school, outside the Party was not to come to school to see about / condition SMP Negeri 8, quite simply through the website alone know the circumstances of SMP Negeri 8 this. The method used is the SDLC systems development method Niagara (Waterfall). With this system is expected to be easier for the public to know SMP Negeri 8 and enables the school to introduce the school.